Navigating complex agricultural challenges: harnessing microbial solutions for sustainable growth and resilience - Monjezi, Nadia; Eisvand, Hamid Reza; Lee, Robert; Levi, Meir; Smith, Donald L. (Frontiers in Agronomy, 2025)
This study explores the potential of Cell-Free Supernatants (CFSs) derived from beneficial bacteria as a sustainable solution to enhance crop resilience in the face of environmental stress. In the context of climate change and soil salinity, CFSs emerge as a promising tool to mitigate crop losses and safeguard food security. By employing bioactive compounds extracted from microbial cultures, CFSs offer a reliable approach to support plant growth and fight abiotic stressors. The research emphasizes the effectiveness of CFSs in promoting seed germination and improving overall plant health, particularly under salinity stress. Additionally, it highlights the role of CFSs in enhancing nutrient absorption and improving plant defense mechanisms, contributing to agricultural sustainability. Despite technical limitations associated with microbial formulations, CFSs provide an alternative to conventional methods, presenting scalable and eco-friendly solutions. Among various production methods of the CFS, centrifugation only and centrifugation plus 0.22 µm filtration stand out due to their simplicity, and efficiency. However, the absence of field-level studies reveals a critical research gap, necessitating further evaluation of CFS performance under real agricultural conditions. Through collaborative research works and innovative application methods, CFSs hold the potential to transform modern agriculture, ensuring resilient crop production systems and global food security for generations to come.